Pelatihan Ecoprint sebagai Peluang Usaha Ramah Lingkungan di Desa Terentang Baru Kecamatan Batin XXIV - Bangun Joko Laksono; Sri Harimurti; Ratna Dewi; Nadiva Febrianty; Melda Fitri; Wiwinarsih Wiwinarsih; Rima Puspita; Nur Jana; Rico Setiawan (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Terentang Baru Village is in the Batin XXIV District, Batang Hari Regency, which is 25 km from the sub-district capital. The area reaches 2,551.6 ha, with a population of 2,972 people. The population has the potential to be developed, the skills they have can form reliable and quality human resources. Ecoprint training is a simple, natural way of adding color to fabric by paying attention to local wisdom. Ecoprinting is done by using existing plants such as leaves, twigs and flowers without chemicals so it is very environmentally friendly. Ecoprint can be used as a business opportunity that produces art products with high selling value, which can increase people's income and economy. The aim of this service activity is (1) to improve the skills of the community in Terentang Baru Village, and (2) to create environmentally friendly business opportunities in Terentang Baru Village. The location of the activity was carried out in Terentang Baru Village, Bhatin XXIV District, Batang Hari Regency on September 14 2024 involving 6 students and 3 lecturers. The target of the activity is the people of Terentang Baru Village. The type of activity consists of an initial stage in the form of observation, followed by counseling and training which is the core stage of the activity. The final stage of the activity was evacuation. The evaluation results show that they strongly agree with the ecoprint training, which is one of the product trends that uses environmentally friendly natural dyes and is profitable for business. Ecoprint skills can create jobs, which are competitive with new innovations.